Dampak Implementasi PSAK 73 Terhadap Kinerja Keuangan, Kebijakan Dividen, dan Manajemen Laba pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Yesi Angraini; Liza Alvia (International Forum of Researchers and Lecturers, 2026)
The implementation of PSAK 73, which adopted IFRS 16, brought fundamental changes to lease financial reporting, triggering various challenges for financial performance and corporate policy. The primary issue examined in this literature was the impact of lease capitalization on financial ratios, dividend policy, and potential earnings management. The overall objective of this study was to evaluate the differences in financial performance before and after the implementation of the new standard, as well as to identify the determinants of dividend policy across various sectors. The dominant method employed was a quantitative approach using comparative analysis and panel data regression on companies listed on the Indonesia Stock Exchange. Key findings indicated that the implementation of PSAK 73 significantly increased total assets and liabilities (leverage), yet tended to decrease profitability ratios such as Return on Assets (ROA) and Return on Equity (ROE). Furthermore, dividend policy was found to be significantly influenced by profitability and the new capital structure resulting from lease capitalization